2019
DOI: 10.1007/s12520-019-00822-7
|View full text |Cite
|
Sign up to set email alerts
|

High status diet and health in Medieval Lisbon: a combined isotopic and osteological analysis of the Islamic population from São Jorge Castle, Portugal

Abstract: This paper presents the first bioarchaeological study of Islamic diet and lifeways in medieval Portugal. Stable isotopes of δ 13 C and δ 15 N and osteological and paleopathological analyses are combined to explore the diet and health status of 27 humans buried within São Jorge Castle, Lisbon (eleventh to twelfth century), interpreted as a high status population. Human isotopic data are considered alongside an animal baseline comprised of 30 specimens sampled from nearby Praça da Figueira, including the main do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 83 publications
1
36
0
Order By: Relevance
“…Nevertheless, Alaica et al (2018) found that among a population of Late Roman-Early Byzantine individuals from Ibiza, women tended to consume more C 4 crops. Toso et al (2019) also report sex differences in diet among the high-status (but not low status) individuals of São Jorge Castle in Lisbon, revealing that men consumed more higher trophic level protein than females and non-adults, which was hypothesised to reflect the division of male and female roles within the elite Islamic household.…”
Section: Historic Foodways: Transition Culture and Religionmentioning
confidence: 83%
See 4 more Smart Citations
“…Nevertheless, Alaica et al (2018) found that among a population of Late Roman-Early Byzantine individuals from Ibiza, women tended to consume more C 4 crops. Toso et al (2019) also report sex differences in diet among the high-status (but not low status) individuals of São Jorge Castle in Lisbon, revealing that men consumed more higher trophic level protein than females and non-adults, which was hypothesised to reflect the division of male and female roles within the elite Islamic household.…”
Section: Historic Foodways: Transition Culture and Religionmentioning
confidence: 83%
“…Figure 1 depicts the locations of the sites included in the publications in this volume. Coastal, inland areas and surrounding islands are well-represented, but the majority them are focused on the modern geopolitical area of Spain (16/19) with two in Portugal (Curto et al 2018;Toso et al 2019) and one considering sites across the Iberian Peninsula as a whole (Cubas et al 2018, not depicted in Fig. 1).…”
Section: Chronological and Geographical Scope Of The Contributionsmentioning
confidence: 99%
See 3 more Smart Citations